BUSINESS-COMMUNITY PARTNERSHIPS: THE LINK WITH SUSTAINABLE LOCAL TOURISM DEVELOPMENT IN TANZANIA? - DIEDERIK DE BOER; MEINE PIETER VAN DIJK; LAURA TARIMO Researcher, Round Table Africa, Maastrich (Tourism & Management Studies)
This paper investigates whether BusinessCommunity Partnerships (BCP) can facilitate local private sector development in Africa. This study offers a new approach to such partnerships by looking at them from a local private sector development perspective using value chain analysis. Focusing on Tanzania, this paper analyses nine tourism business-community partnership cases including three NGO-initiated partnerships, three business-initiated partnerships and three cases in which there was no explicit partnership between the business and the community. Five effects of tourism development are assessed by such partnerships, namely access to capital, access to skills/ knowledge, access to markets, access to infrastructure and access to land. Overall, business initiated Business–Community Partnerships contributed positively to access of markets and access to infrastructure. The NGO-initiated partnerships contribute positively to the access of land and improved in certain cases the access to infrastructure and markets. However, appropriate transfer of entrepreneurship knowledge and access to capital remains very inadequate. This study offers a new approach by looking at partnerships from a local private sector dev